QUESTIONS AND QUESTIONING SKILLS IN ELT - Supriusman Supriusman (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: Question and questioning skill have a very important role to play in motivating students to learn. Besides, questioning is a very special term in English language teaching (ELT) because it is one of the basic skills of teaching, one of the components of scientific approach that a teacher applies in the main or core activities in teaching and learning process, and one of the components of the CTL approach that a teacher also applies in ELT. Therefore, it is believed that this topic is useful for English teachers because they can improve their comprehension and then implement their experience and knowledge in the field. In addition, this paper describes about the term of question, types of question, question categories or levels of question, purposes of questions, and wait time. It is expected this paper is useful to improve English teachers‟ knowledge and skill, and they can use this theoretical and practical knowledge to promote the participation of their students to be active in ELT in the classroom.Key words: questions, questioning skills, and question levels or categories